Myelodysplastic syndromes are propagated by rare and distinct human cancer stem cells in vivo. - Woll, P; Kjällquist, U; Chowdhury, O; Doolittle, H; Wedge, D; Thongjuea, S; Erlandsson, R; Ngara, M; Anderson, K; Deng, Q; Mead, A; Stenson, L; et al. (Cell Press, 2014)
Evidence for distinct human cancer stem cells (CSCs) remains contentious and the degree to which different cancer cells contribute to propagating malignancies in patients remains unexplored. In low- to intermediate-risk myelodysplastic syndromes (MDS), we establish the existence of rare multipotent MDS stem cells (MDS-SCs), and their hierarchical relationship to lineage-restricted MDS progenitors. All identified somatically acquired genetic lesions were backtracked to distinct MDS-SCs, establishing their distinct MDS-propagating function in vivo. In isolated del(5q)-MDS, acquisition of del(5q) preceded diverse recurrent driver mutations. Sequential analysis in del(5q)-MDS revealed genetic evolution in MDS-SCs and MDS-progenitors prior to leukemic transformation. These findings provide definitive evidence for rare human MDS-SCs in vivo, with extensive implications for the targeting of the cells required and sufficient for MDS-propagation.